Moral Distress in Hospitals During the First Wave of the COVID-19 Pandemic: A Web-Based Survey Among 3,293 Healthcare Workers Within the German Network University Medicine - Schneider, Juliane Nora; Hiebel, Nina; Kriegsmann-Rabe, Milena; Schmuck, Jonas; Erim, Yesim; Morawa, Eva; Jerg-Bretzke, Lucia; Beschoner, Petra; Albus, Christian; Hannemann, Julian; Weidner, Kerstin; Steudte-Schmiedgen, Susann; et al. (Frontiers in Psychology, 2021)
Objective: The present study aimed to investigate the correlation between moral distress and mental health symptoms, socio-demographic, occupational, and COVID-19-related variables, and to determine differences in healthcare workers' (HCW) moral distress during the first wave of the COVID-19 pandemic. Method: Data from 3293 HCW from a web-based survey conducted between the 20th of April and the 5th of July 2020 were analyzed. We focused on moral distress (Moral Distress Thermometer, MDT), depressive symptoms (Patient Health Questionnaire-2, PHQ-2), anxiety symptoms (Generalized Anxiety Disorder-2, GAD-2), and increased general distress of nurses, physicians, medical-technical assistants (MTA), psychologists/psychotherapists, and pastoral counselors working in German hospitals. Results: The strongest correlations for moral distress were found with depressive symptoms, anxiety symptoms, occupancy rate at current work section, and contact with SARS-CoV-2. Nurses and MTA experienced significantly higher moral distress than physicians, psychologists/psychotherapists, and pastoral counselors. The average level of moral distress reported by nurses from all work areas was similar to levels which before the pandemic were only experienced by nurses in intensive or critical care units. Conclusion: Results indicate that moral distress is a relevant phenomenon among HCW in hospitals during the COVID-19 pandemic, regardless of whether they work at the frontline or not and requires urgent attention.